EFFICACY OF PATRA POTTALI SWED & JANUBASTI IN OSTEOARTHRITIS W.S.R. TO KNEE JOINT (JANU-SANDHIVATA) - Sharma, *Gyan Prakash; Sharma, Meenakshi; Sharma, Mahesh Kumar (International Journal of Ayurveda and Pharma Research, 2015)
Osteoarthritis (OA) is a chronic degenerative disease in male while it affects female in younger age. Life style play major role in OA. In Osteoarthritis (Sandhigata vata) pain, swelling, restricted movements of joints are common clinical features. The insidious starting is with aching pain in the joint and relieved by the rest. The other associated symptom is stiffness, which aggravated after a long rest and subsides after by active movement. In this trial entitled efficacy of Patra pottli swed & Janubasti in osteoarthritis w.s.r. to knee joint (Janu-sandhivata) Patra pottali swed & janu basti are selected to treat the Osteoarthritis of knee joint (Janu sandhigata vata) for 90 patients. All the 90 patients were divided in three groups of 30 patients in each group with an Patra Pottali Swed (Nirgundi Patra), Janubasti (Dashmooladi tail) & combined therapy (Patra Pottali Swed & Janu basti).Swedan is indicated in Kapha vata pradhan vyadhi. swedan helps in remove stiffness, pain, heaviness and coldness. In this trail both therapy Patra pottali sed and Kati basti have based on Swedan properties. Acharya charak mentioned in Sagni swed (sankar swed) for Pottali seed. Both therapy are special indicate in Group– A (Patra Pottali Swed) & Group – B (Janubasti) are mild beneficial, statistically significant & Group – C (Patra Pottali Swed & Janu basti) is moderate beneficial, statistically highly significant.